Gauging U(1) symmetries and the number of right-handed neutrinos - Montero, J. C. [UNESP]; Pleitez, V. [UNESP] (Elsevier B.V., 2009)
In this Letter we consider that assuming: (a) that the only left-handed neutral fermions are the active neutrinos, (b) that B - L is a gauge symmetry, and (c) that the L assignment is restricted to the integer numbers, the anomaly cancellation imply that at least three right-handed neutrinos must be added to the minimal representation content of the electroweak standard model. However, two types of models arise: (i) the usual one where each of the three identical right-handed neutrinos has total lepton number L = 1: (ii) and the other one in which two of them carry L = 4 while the third one carries L = -5. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Right-handed neutrinos; Local B - L symmetry; Multi-Higgs models